Adaptive Servo-Ventilation: A Comprehensive Descriptive Study in the Geneva Lake Area - Cantero, Chloé; Adler, Dan; Pasquina, Patrick; Uldry, Christophe; Egger, Bernard; Prella, Maura; Younossian, Alain Bigin; Poncet, Antoine; Soccal-Gasche, Paola; Pepin, Jean-Louis; Janssens, Jean-Paul (Frontiers in Medicine, 2020)
Background: Use of adaptive servo-ventilation (ASV) has been questioned in patients with central sleep apnea (CSA) and chronic heart failure (CHF). This study aims to detail the present use of ASV in clinical practice. Methods: Descriptive, cross-sectional, multicentric study of patients undergoing long term (≥3 months) ASV in the Cantons of Geneva or Vaud (1,288,378 inhabitants) followed by public or private hospitals, private practitioners and/or home care providers. Results: Patients included (458) were mostly male (392; 85.6%), overweight [BMI (median, IQR): 29 kg/m2 (26; 33)], comorbid, with a median age of 71 years (59–77); 84% had been treated by CPAP before starting ASV. Indications for ASV were: emergent sleep apnea (ESA; 337; 73.6%), central sleep apnea (CSA; 108; 23.6%), obstructive sleep apnea (7; 1.5%), and overlap syndrome (6; 1.3%). Origin of CSA was cardiac (n = 30), neurological (n = 26), idiopathic (n = 28), or drug-related (n = 22). Among CSA cases, 60 (56%) patients had an echocardiography within the preceding 12 months; median left ventricular ejection fraction (LVEF) was 62.5% (54–65); 11 (18%) had a LVEF ≤45%. Average daily use of ASV was [mean (SD)] 368 (140) min; 13% used their device <3:30 h. Based on ventilator software, apnea-hypopnea index was normalized in 94% of subjects with data available (94% of 428). Conclusions: Use of ASV has evolved from its original indication (CSA in CHF) to a heterogeneous predominantly male, aged, comorbid, and overweight population with mainly ESA or CSA. CSA in CHF represented only 6.5% of this population. Compliance and correction of respiratory events were satisfactory. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04054570.